Maternal feelings about the hospitalization of the premature child: Content analysis - Pinto, Keli Regiane Tomeleri da Fonseca; Pinhatti, Evelin Daiane Gabriel; Zani, Adriana Valongo; Parada, Cristina Maria Garcia de Lima [UNESP] (Escola de Enfoermagem Aurora de Afonso Costa, 2017)
Aim: understand the feelings experienced by the mother when having her premature child hospitalized in the Neonatal Intensive Care Unit (NICU). Method: Descriptive research of a qualitative nature, performed with 11 mothers, through a semi-structured interview. The Content Analysis framework was adopted. Results: three thematic categories were identified: Suffering from the hospitalization of the premature child; Premature child care: trust in the team; Experiencing the impact of the neonatal intensive care environment. Discussion: mothers were faced with feelings such as fear, guilt over suffering and possible loss of the child, and reported feeling powerless and unable to care for the child at this time, which increased their anguish. Conclusion: mothers, when faced with the premature child in the NICU, experienced different feelings, feeling incapable and, often, moving away from the newborn. However, they reported confidence and security in the care of professionals with their children, valuing both technical aspects and interpersonal relationships.

Objetivo: comprender los sentimientos que la madre experimenta al tener su hijo prematuro internado en una Unidad de Terapia Intensiva Neonatal (UTIN). Método: investigación descriptiva de naturaleza cualitativa, realizada con 11 madres, por medio de una entrevista semiestructurada. Se adoptó el referencial del Análisis de Contenido. Resultados: se identificaron tres categorías temáticas: Sufrimiento por la hospitalización del hijo prematuro; El cuidado del hijo prematuro: confianza en el equipo; Viviendo el impacto del ambiente de terapia intensiva neonatal. Discusión: las madres se depararán con sentimientos como miedo, culpa por el sufrimiento y la posible pérdida del hijo, y refieren sentirse impotentes e incapaces de cuidar del hijo en este momento, lo que aumentó sus angustias. Conclusión: las madres, al tener a sus hijos prematuros en la UTIN, experimentan sentimientos diversos, sintiéndose incapaces lo que hace que muchas veces, se aparten del recién nacido. Sin embargo, relataron sentir confianza y seguridad en el cuidado que los profesionales les ofrecen a sus hijos, valorizando tanto aspectos técnicos como las relaciones interpersonales.
Sentimientos maternos frente a la hospitalización del hijo prematuro: Análisis de contenido
Keywords: Infant; Intensive Care Units; Mother-child relations; Neonatal; Premature; Recién nacido prematuro; Relaciones madre-hijo; Unidades de Cuidado Intensivo Neonatal